The role of social aspects in the integration of the professionally disabled worker (Case study in The City of Laghouat) - Meroua BENTOUATI; Saida ZIZAH (Social Sciences Journal, 2022)
Since professional integration is an integral part of the general integration and includes the worker's compatibility with his or her work environment, the working individual must achieve greater compatibility in his or her professional environment, where the social aspects prevailing within the institution are among the most important factors affecting the integration process, which in turn reflects the worker's performance and degree of harmony in his work. This is why we will try to point out the most important social aspects that will significantly affect the disabled worker by studying the situation of disabled workers in some institutions located at the level of the city of Laghouat.